Boosting spatial resolution by incorporating periodic boundary conditions into single-distance hard-x-ray phase retrieval. (13th October 2020) - Paganin, David M; Favre-Nicolin, Vincent; Mirone, Alessandro; Rack, Alexander; Villanova, Julie; Olbinado, Margie P; Fernandez, Vincent; da Silva, Julio C; Pelliccia, Daniele
Abstract: A simple coherent-imaging method due to Paganin et al is widely employed for phase–amplitude reconstruction of samples using a single paraxial x-ray propagation-based phase-contrast image. The method assumes that the sample-to-detector distance is sufficiently small for the associated Fresnel number to be large compared to unity. The algorithm is particularly effective when employed in a tomographic setting, using a single propagation-based phase-contrast image for each projection. Here we develop a simple extension of the method, which improves the reconstructed contrast of very fine sample features. This provides first-principles motivation for boosting fine spatial detail associated with high Fourier frequencies, relative to the original method, and was inspired by several recent works employing empirically-obtained Fourier filters to a similar end.